Souvenirs: Their Role In Tourism Industry, Cultural Heritage And Their Utilization In Experiential Teaching - Balermpas, A.; Manola, M. (Archives of Business Research, 2020)
This article presents research that examines souvenirs and their role in tourism and consequentially in a country’s economy. Its purpose is to examine their importance and contribution to the local community by encouraging local economic growth as well as their educational importance and how teachers can use them as starting point for experientially teaching cultural heritage through practical application of art and history in the educational learning process.